Approximate Controllability of Stochastic Fractional Neutral Impulsive Integrodifferential Systems with State Dependent Delay and Poisson Jumps - Selvarasu, S.; Arjunan, M. Mallika (Journal of Applied Nonlinear Dynamics, 2026)
The purpose of this manuscript is to study the approximate controllability of stochastic fractional impulsive neutral integro-diﬀerential equations with state dependent delay and Poisson jumps by using ﬁxed point techniques. By the help of stochastic analysis theory and fractional calculus, we have derived the controllability results. Finally, an example is given to illustrate the obtained abstract result.